2021
DOI: 10.1108/medar-01-2021-1174
|View full text |Cite
|
Sign up to set email alerts
|

From little seeds to a big tree: a far-reaching assessment of the integrated reporting stream

Abstract: Purpose The purpose of this paper is to provide the first assessment of the integrated reporting (IR) stream using a broad sample of publications separated into research scopes (accounting and non-core accounting journals) and using a longitudinal perspective. This study proposes to identify its main contributors, evidencing both individual and collaborative work. Design/methodology/approach Bibliometric tools supported by a milestone approach to IR history were used to address the first two research questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The bibliometric analysis provides an overview of the relationship, volume and impact of the research (Lopes and Penela, 2022). Bibliometric tools, including keyword co-occurrence analyses, are applied to the practical and academic sources (Van Eck and Waltman, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bibliometric analysis provides an overview of the relationship, volume and impact of the research (Lopes and Penela, 2022). Bibliometric tools, including keyword co-occurrence analyses, are applied to the practical and academic sources (Van Eck and Waltman, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This is indicative of articles which have connected themes (Caputo et al ., 2021). In line with other bibliometric studies (Lopes and Penela, 2022), VOSviewer software (see Van Eck and Waltman, 2017) is used to generate textual and graphic representations of the results. The connected keywords resulted in three clusters of themes developing and these points served as open codes and were recorded in a “data mind map” (adapted from: Holland, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis allows for the research themes and future avenues of research for integrated thinking as a concept to be identified and developed (see Section 7). In line with other bibliometric studies (Bellucci et al, 2020;Lopes and Penela, 2021), VOSviewer software (see Van Eck and Waltman, 2017) is used to generate textual and graphic representations of the results.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…The bibliometric analysis provides an overview of the relationship, volume and impact of the research through various techniques, frequency analysis, citation analysis, authorship and country affiliation analysis (Lopes and Penela, 2021; Zupic and Čater, 2015). Bibliometric tools including citation, co-citation, bibliographic-coupling and keyword co-occurrence analyses are applied to the 98 academic sources (Van Eck and Waltman, 2017).…”
Section: Search Protocolmentioning
confidence: 99%
See 1 more Smart Citation